2017
DOI: 10.1002/aid2.12128
|View full text |Cite
|
Sign up to set email alerts
|

Performance of quantitative immunochemical test for fecal hemoglobin for surveillance of colorectal neoplasia after polypectomy in clinical practice

Abstract: Summary Aims We examined the yield of immunochemical test for fecal hemoglobin (FIT) for the post‐polypectomy individuals in a colorectal cancer screening program. Methods We enrolled 50‐75 years average‐risk individuals who attended a biennial FIT‐based colorectal cancer screening program from March 2010 to December 2011 (index round) and from January 2012 to December 2013 (repeated round). Colonoscopy was recommended to the participants with an FIT ≧ 30 μg Hb/g feces. Participants identified with adenomas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recently, a large retrospective cohort study reported that not only the FIT positivity rate but also the adenoma detection rate was significantly higher in the post‐polypectomy surveillance group compared with the repeated screening group [14]. The authors concluded that FIT may play a role for post‐polypectomy surveillance.…”
mentioning
confidence: 99%
“…Recently, a large retrospective cohort study reported that not only the FIT positivity rate but also the adenoma detection rate was significantly higher in the post‐polypectomy surveillance group compared with the repeated screening group [14]. The authors concluded that FIT may play a role for post‐polypectomy surveillance.…”
mentioning
confidence: 99%